2004
DOI: 10.1021/jf030520o
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Photolysis of Niclosamide

Abstract: The photodegradation of [(14)C]niclosamide was studied in sterile, pH 5, 7, and 9 buffered aqueous solutions under artificial sunlight at 25.0 +/- 1.0 degrees C. Photolysis in pH 5 buffer is 4.3 times faster than in pH 9 buffer and 1.5 times faster than in pH 7 buffer. In the dark controls, niclosamide degraded only in the pH 5 buffer. After 360 h of continuous irradiation in pH 9 buffer, the chromatographic pattern of the degradates was the same regardless of which ring contained the radiolabel. An HPLC metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 21 publications
(25 reference statements)
4
30
0
Order By: Relevance
“…A polar peak at 3.7 min was apparent in individual sampling points of soils of 1.5-mm and less depths. This peak is similar to degradates reported in the aqueous photolysis of niclosamide in pH 9 buffer (15). In that study a 3-min peak was discovered to be made up of carbon dioxide and several organic acids, indicating complete breakdown of the aromatic ring system.…”
Section: Light Transmittance In Relation To Soil Depthsupporting
confidence: 84%
“…A polar peak at 3.7 min was apparent in individual sampling points of soils of 1.5-mm and less depths. This peak is similar to degradates reported in the aqueous photolysis of niclosamide in pH 9 buffer (15). In that study a 3-min peak was discovered to be made up of carbon dioxide and several organic acids, indicating complete breakdown of the aromatic ring system.…”
Section: Light Transmittance In Relation To Soil Depthsupporting
confidence: 84%
“…2-C-4-NA is also reported as a photolysis product of niclosamide [4]. Espinosa-Aquirre et al [5] reported the metabolism of niclosamide, which is used as an anti-helminthic drug, results in the formation of 2-C-4-NA and 5-chlorosalicylic acid metabolites by hydrolytic cleavage of amide bond.…”
Section: Introductionmentioning
confidence: 99%
“…The polar materials formed in both aquatic studies are very similar in nature to polar degradates observed in the aqueous photolysis of niclosamide (15). Niclosamide was found to be completely photolyzed in pH 9 buffer into carbon dioxide and five or six aliphatic acids.…”
Section: Discussionmentioning
confidence: 52%